Strategi Meningkatkan Potensi Kecerdasan Visual-Spasial Peserta Didik di Tingkat Sekolah Dasar - Faridah, Zeni; Muzakki, Ahmad (Madrasah Ibtidaiyah Education Journal, 2024)
Visual-spatial intelligence is an individual's ability to understand, recognize, and manipulate objects in space effectively. Developing visual-spatial intelligence is very important at the elementary school level because it can support students' academic and non-academic achievements and creative thinking skills. This research aims to formulate an effective strategy for increasing the visual-spatial intelligence potential of students at the elementary school level through a literature review. This research uses library research methods, where data is obtained from various relevant literature, such as books, scientific journals, articles, and previous research results. These sources are analyzed to find and formulate learning strategies that educators can apply. The research results show that using media such as maps, pictures, logos, puzzles, diagrams, and others, as well as project-based activities such as making models or works of art, can stimulate students' visual-spatial intelligence. In addition, interactive learning environments and digital technology such as visualization applications have also proven effective. This research concludes that combining visual media, practical activities, and digital technology is a strategy that can help develop visual-spatial intelligence at the elementary school level.